Bilateral Anterior Ischemic Optic Neuropathy During Treatment with Pegylated Interferon and Ribavirin - Rinehart, Jason; Stottlemyer, Lisa (Canadian Journal of Optometry, 2016)
Hepatitis C virus (HCV) is a blood-borne pathogen that often results in chronic liver infection leaving patients at risk for cirrhosis, liver decompensation and hepatocellular carcinoma. The goal of therapy is to eliminate the virus in order to minimize morbidity and mortality from HCV infection. Traditional treatment has utilized a combination of pegylated-interferon (IFN) and ribavirin that often causes both systemic and ocular side effects. The most common ocular side effects are retinal hemorrhages and cotton wool spots, although in rare circumstances more significant ophthalmic adverse events have been attributed to IFN therapy. Here we discuss a case of bilateral anterior ischemic optic neuropathy (AION) that occurred during treatment with IFN and ribavirin for HCV genotype 1. We review the proposed pathogenesis of ocular side effects associated with this regimen, as well as the pathogenesis and risk factors associated with AION itself. Finally, we will offer clinical recommendations for screening for more than retinopathy should a patient present with ophthalmic complications.